Indicators to the consumption of electric energy and agriculture cattle farming production for the elaboration of clusters with cities of the state of São Paulo, Brazil - Oliveira, Paulo Andre de; Simon, Elias José [UNESP] (My University, 2012)
The issue in this matter is that rules for use of electricity in rural areas are limited to the provision of inputs. Adopting guidelines to consider managed sub regions can generate poor results. The focus of this study was to present parameters for indicators of electric energy and agricultural production to allow the formation of city groups in Sao Paulo State, Brazil, with similar electric energy consumption and rural agricultural production. The methodology was the development of indicators that characterize the electric energy consumption/agricultural production and the preparation of groups using indicators with ward of statistical method of groups. The main conclusions were the formation of six homogeneous groups with similar characteristics regarding agricultural production/consumption of electricity. The application of these groups in cities with similar characteristics would produce more satisfactory results than the division of administrative Rural Development Offices (RDO).
Keywords: Clusters; Indicators; Productive energy